Post‐operative complications following apocrine gland anal sac adenocarcinoma resection in dogs. (29th July 2021) - Sterman, Allyson; Butler, J. Ryan; Chambers, Aidan; Dickson, Rachel; Dornbusch, Josephine; Mickelson, Megan; Selmic, Laura; Scharf, Valerie; Schlag, Ariel; Skinner, Owen; Vinayak, Arathi; Janssens, Brandan Wustefeld
Abstract: Describe the complications associated with surgical resection of primary apocrine gland anal sac adenocarcinoma (AGASACA) tumours study design multi‐institutional retrospective cross‐sectional cohort study Animals Client owned dogs with spontaneous disease using the Clavien‐Dindo classification system, post‐operative events were assigned and described. Logistic regression analysis was used to analyse for risk factors for a significant association with complications. One hundred sixty‐one dogs were included in the analysis. The post‐operative sequelae, complication, and failure to cure rates specific to the anal sac site was 14%, 17% and 1%, respectively. The majority (68%) of complications were grade II or higher, therefore requiring some form of intervention. Intra‐operative complications were identified in 11 cases (7%) with anorectal wall perforation being most common. An intra‐operative complication was significantly associated with post‐operative complications (p < 0.001; OR 7.4) while anorectal wall perforation was the only significant risk factor on regression analysis (p < 0.001; OR 19). Surgical site infection was identified in 20 of 161 (12%) of cases. Local recurrence (LR) occurred in 18% of cases at a median of 374 days (95% CI: 318–430). The only risk factor significantly associated with LR was the presence of vascular or lymphatic invasion (p = 0.008; OR 3). Post‐operative complications were relatively infrequent but the risk was significantly increased when there was an intraoperative complication during resection of a primary AGASACA tumour. This study provides information for the clinician regarding risk factors for post‐operative complications.